2019
DOI: 10.1002/syn.22100
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies alters spine number in cortical and subcortical limbic brain regions of old rats

Abstract: Pregnancy is a complex process, involving a number of hormones and trophic factors, many of which are formed in the placenta. Several of these trophic factors have an effect at the neuronal level, such as BDNF. Consequently, recent reports have shown that exposure to these hormones (estrogen and progesterone) and trophic factors such as BDNF exert a neuroprotective effect. Here, we study the effect of the number of pregnancies on dendritic morphology of aged female rats (18 months of age). Rats of the 18‐month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…Previous reports have shown that aging caused a reduction in locomotor activity (Flores‐Vivaldo et al., 2019; Insgrama & Jucker, 1999; Lafoux, Baudry, Bonhomme, Le Ruyet, & Huchet, 2016; Yu, Xu, Song, Ji, & Zhang, 2013). For this reason, we analyzed whether the PBA has an effect on this type of behavior.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports have shown that aging caused a reduction in locomotor activity (Flores‐Vivaldo et al., 2019; Insgrama & Jucker, 1999; Lafoux, Baudry, Bonhomme, Le Ruyet, & Huchet, 2016; Yu, Xu, Song, Ji, & Zhang, 2013). For this reason, we analyzed whether the PBA has an effect on this type of behavior.…”
Section: Resultsmentioning
confidence: 99%
“…This cognitive improvement was not related to an increase in locomotor activity in a new environment. It is also well‐known that, like cognition, locomotive activity is also reduced with aging (Alcantara‐González et al, 2012; Flores‐Vivaldo et al., 2019; Insgrama & Jucker, 1999; Lafoux et al., 2016; Yu et al., 2013). However, our results suggest that the PBA did not modify locomotive activity in a novel environment in the old mice, despite producing an improvement in the number of dendritic spines and markers for synaptophysin without changes in the total dendritic length in the NAcc, a structure related to this behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations